2019
DOI: 10.1007/jhep10(2019)135
|View full text |Cite
|
Sign up to set email alerts
|

Boundary-to-bulk maps for AdS causal wedges and RG flow

Abstract: We consider the problem of defining spacelike-supported boundary-to-bulk propagators in AdS d+1 down to the unitary bound ∆ = (d − 2)/2. That is to say, we construct the 'smearing functions' K of HKLL but with different boundary conditions where both dimensions ∆ + and ∆ − are taken into account. More precisely, we impose Robin boundary conditions, which interpolate between Dirichlet and Neumann boundary conditions and we give explicit expressions for the distributional kernel K with spacelike support. This fl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 30 publications
2
10
0
Order By: Relevance
“…• As Z → 0 our fermion fields have the requisite behavior (17). To see this note that the region of integration becomes very small as Z → 0, so one can bring the CFT operators out of the integral and explicitly verify the Z → 0 behavior.…”
Section: Ads Odd Smearing Functionsmentioning
confidence: 95%
See 3 more Smart Citations
“…• As Z → 0 our fermion fields have the requisite behavior (17). To see this note that the region of integration becomes very small as Z → 0, so one can bring the CFT operators out of the integral and explicitly verify the Z → 0 behavior.…”
Section: Ads Odd Smearing Functionsmentioning
confidence: 95%
“…This condition also avoids poles in the gamma functions. If the condition m > d 2 − 1 2 is violated we expect that the smearing functions (27) should be replaced with distributions, as noted for scalar fields in [13,16,17]. But we leave an exploration of this issue to future work.…”
Section: Ads Odd Smearing Functionsmentioning
confidence: 96%
See 2 more Smart Citations
“…It was found that in this case the support of the smearing function is the intersection of the light-cone of the bulk point and the boundary. In [21] the range of allowed ∆ was extended to d/2 ≤ ∆ ≤ d − 1 by analytic continuation. Our purpose here is to find a direct derivation of the generalized HKLL formula for ∆ values below the original lower bound d − 1.…”
Section: Jhep02(2022)015mentioning
confidence: 99%